Effects of acetazolamide on linear growth in children with pseudotumor cerebri syndrome - Sheldon, Claire A.; Reggie, Sara N.; Paley, Grace L.; McCormack, Shana E.; Liu, Grant T. (Frontiers in Ophthalmology, 2023)
Background/introduction While oral acetazolamide is a cornerstone of management of adult and pediatric PTCS, previous studies have suggested that acetazolamide used in children with other conditions may influence growth. Aims and methods Retrospective chart review involving a single tertiary medical center. Thirty-four children with definite or probable PTCS were identified. Analysis was restricted to individuals from whom anthropometric data were available before and during acetazolamide treatment (n=22). Results Half of individuals (n=11/22) showed a decline in BMI Z-scores. Sixty-three percent (n=14/22) showed a decrease in height Z-scores during treatment with acetazolamide; in 6 of these 14 children who had complete data, 3 showed at least a partial recovery of height Z-scores after discontinuation of acetazolamide. Conclusion Acetazolamide may be associated with growth suppression in some children treated for pediatric PTCS. In some cases, the growth suppression appears to reverse once the acetazolamide is stopped.